Residential child care in the spotlight: reflections on being involved in the BBC series 'social workers' - G.A. McPheat (Scottish Journal of Residential Child Care)
Describes how a residential unit offering services for 8 children and young people became involved in the BBC Scotland series 'Social Workers', a fly-on-the-wall documentary about Edinburgh's Social Work Department. Discusses how the unit became involved, the filming process, reactions, and some issues raised. The ethics of filming and broadcasting the lives of young people was contentious. Obviously much was lost when 5 months had to be reduced to 30 minutes, but it was generally agreed the results were positive.